Assessment of job Stress Related to Social Environment among Nurses in Cardiac Surgical Intensive Care Units in Baghdad City - Ismael, Bayda'a A.; Jacoub, Shirroq M. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Nurses experience increasing demands in the workplace and have limited support in their occupation to help them lowering the level of stress, and one of the observable severities of stress among nurses in intensive care units are the social Stressors. So the study was aimed to assess the social stressors and the severity of stress among nurses in cardiac surgical intensive care units.Objectives: The study aimed to assess the level and sources of social job stress related to the social relationship experienced by nurses, who were working in intensive care units and to find out the relationship between social stressors and some variables such as age, gender, educational level, marital status, Years of experience in cardiac intensive care units.Patients and Methods: A descriptive-analytic Study was conducted on cardiac surgical intensive care units nurses in Baghdad hospitals. The sample of the study were selected purposively and consisted of 60 nurses who were working in cardiac surgical intensive care units in Baghdad city (Ibn Al- Bitar Hospital for Cardiac Surgery, Ibn Al-Nafis Hospital for Cardiovascular Diseases, and the Iraqi Center for Heart Diseases) in the period of 1st February 2006 to the 6th April 2006. Data was collected through the use of the constructed questionnaire and the process of the self- administrative report for each nurse as a mean of data collection methods.A Questionnaire was designed to consist two parts; the first part concerned with the demographic characteristics of the sample and the second part concerned with the social environmental stressors, and it contain 14 items describing the social stressors. Data was analyzed through the application of the descriptive statistical analysis (frequency, percentage, mean, standard division, and mean of score) and inferential statistic (chi-Squire test).Results: The results of the study revealed that the most of sample were female (53 %), their age ranged between (30-39) years, of university graduates, single, with (6-10) experience in cardiac surgical intensive care units. Also the results revealed that nurses in cardiac surgical intensive care units suffer from severe level of stress related to the social environmental stressor RS. (67.69 %).Conclusions: Nurses who were working in intensive care units suffered from sever job stress related to the workplace stressors, and there is a significant relationship between social job stress and nurses age. Therefore there was a need for an effective stress management to assist such nurses to deal with job stress.